Kepuasan Kerja dan Loyalitas Generasi-Y - Rohimat Nurhasan (Fakultas Ekonomi Universitas Garut, 2018)
This research is based on the view that employee loyalty is one of the important factors that can determine a company to survive in any tough competition. High employee loyalty can be obtained, among others, if the company can meet employee job satisfaction. The purpose of this study was to analyze Y-generation employee loyalty which is influenced by job satisfaction. The method used is descriptive and verification, with a total sample of all Y-generation employees who work at Higher Education in Garut Regency with 132 respondents. The sampling technique uses a saturated sample approach or a census. Data collection was carried out through interviews, questionnaires and surveys. The data analysis used was the statistical approach of path analysis with the help of SPSS 20.0 software. The results showed that job satisfaction on employee loyalty was not significant. This means that even though job satisfaction is obtained, it does not mean that Y-generation employees will be loyal to their current company.